Ageism Through the Informational Practices During Health Crisis: A Qualitative Study Among Older Adults in Quebec (Canada) - Nicolai Guzun; André Tourigny; Eve Dubé; Alexandre Coutant; Maryline Vivion (Journal of Ageing and Longevity)
This study explores the health-information-seeking practices of older adults. Conducted in Quebec, Canada, this qualitative research involved semi-structured interviews with 36 participants aged 60 and over, between 19 July and 20 August 2021, during the COVID-19 pandemic. The interviews, carried out via online platforms and telephone, focused on information sources, the method of information retrieval, and participants’ reflections on and use of pandemic-related information. Thematic content analysis was used to identify the presence of ageism. The study showed that participants favored government press conferences and traditional media, while remaining skeptical of social media. The analysis identified the concept of ageism (institutional, interpersonal, and self-directed) in about half of the interviews, with institutional ageism predominating in communications and actions of authorities and in the portrayal of older adults by media. The findings highlight the need for reliable, respectful communications reaching older adults for effective and relevant public health messages.